2022
DOI: 10.1186/s13099-022-00480-6
|View full text |Cite
|
Sign up to set email alerts
|

Closely related Salmonella Derby strains triggered distinct gut microbiota alteration

Abstract: Background Salmonella Derby is one of the most predominant Salmonella serotypes that seriously threatens food safety. This bacterium can be further differentiated to sub-populations with different population sizes; however, whether and how the S. Derby–gut microbiota interactions affect epidemic patterns of S. Derby sub-populations remain largely unknown. Results We selected two representative strains, 14T and 14C, which represent rarely distribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Also, the depletion of Parabacteroides and Lachnospiraceae_uncultured was confirmed by multiple Salmonella infection models, especially those involving higher virulence Salmonella infection. 56 , 60 While for Ligilactobacillus , a probiotic bacteria used to treat enteric infections, 61 the increased abundance could be utilized by Salmonella to suppress inflammatory response for immune escape as reported here, 62 confirming the negative correlation between it and pro-inflammatory factors. On the other hand, SaaS increased the relative abundance of deleterious bacteria or making general bacteria harmful such as the Mycobacterium .…”
Section: Discussionsupporting
confidence: 68%
“…Also, the depletion of Parabacteroides and Lachnospiraceae_uncultured was confirmed by multiple Salmonella infection models, especially those involving higher virulence Salmonella infection. 56 , 60 While for Ligilactobacillus , a probiotic bacteria used to treat enteric infections, 61 the increased abundance could be utilized by Salmonella to suppress inflammatory response for immune escape as reported here, 62 confirming the negative correlation between it and pro-inflammatory factors. On the other hand, SaaS increased the relative abundance of deleterious bacteria or making general bacteria harmful such as the Mycobacterium .…”
Section: Discussionsupporting
confidence: 68%
“…The anti- Salmonella effects of L. salivarius strains were determined using the agar spot test, as described by Schillinger [ 63 ], with a pathogenic strain S. Derby 14T originating from swine serving as an indicator [ 64 ]. After incubation in MRS liquid medium at 37°C for 24 h, 10 µL of each L. salivarius culture was inoculated in the center of MRS agar plates, air dried, and incubated at 37°C for an additional 24 h. Following this, 10 µL of overnight grown S. Derby 14T culture was added to Luria–Bertani (LB) semi-solid medium and mixed well.…”
Section: Methodsmentioning
confidence: 99%
“…Gut microbiota can control harmful microbial invasion through habitat filters, including diet, host-derived resources, and microbiota-derived metabolites such as short-chain fatty acids [ 17 ]. Many studies have shown that butyric acid, one of the short-chain fatty acids, has the effect of inhibiting Salmonella [ 22 , 23 , 24 ]. Ruminococcaceae [ 25 , 26 ] and Lachnospiraceae [ 27 ] are important producers of butyric acid in the intestine.…”
Section: Discussionmentioning
confidence: 99%